Modifying Anthocyanins Biosynthesis in Tomato Hairy Roots: A Test Bed for Plant Resistance to Ionizing Radiation and Antioxidant Properties in Space - Massa, Silvia; Pagliarello, Riccardo; Cemmi, Alessia; Di Sarcina, Ilaria; Bombarely, Aureliano; Demurtas, Olivia Costantina; Diretto, Gianfranco; Paolini, Francesca; Petzold, H. Earl; Bliek, Mattijs; Bennici, Elisabetta; Del Fiore, Antonella; et al. (Frontiers in Plant Science, 2022)
Gene expression manipulation of specific metabolic pathways can be used to obtain bioaccumulation of valuable molecules and desired quality traits in plants. A single-gene approach to impact different traits would be greatly desirable in agrospace applications, where several aspects of plant physiology can be affected, influencing growth. In this work, MicroTom hairy root cultures expressing a MYB-like transcription factor that regulate the biosynthesis of anthocyanins in Petunia hybrida (PhAN4), were considered as a test bed for bio-fortified tomato whole plants aimed at agrospace applications. Ectopic expression of PhAN4 promoted biosynthesis of anthocyanins, allowing to profile 5 major derivatives of delphinidin and petunidin together with pelargonidin and malvidin-based anthocyanins, unusual in tomato. Consistent with PhAN4 features, transcriptomic profiling indicated up-regulation of genes correlated to anthocyanin biosynthesis. Interestingly, a transcriptome reprogramming oriented to positive regulation of cell response to biotic, abiotic and redox stimuli was evidenced. PhAN4 hairy root cultures HRCs showed significant capability to counteract ROS accumulation and protein misfolding upon high dose gamma irradiation, that is among the most potent pro-oxidant stress that can be encountered in space. These results may have significance in the engineering of whole tomato plants that can benefit space agriculture.